Questões socioambientais do bairro Nova Santa Marta, na cidade de Santa Maria, RS - Cardozo, Sandra Beatriz de Andrade (2013)
The urban growth in Santa Maria, presents an expansion of irregular land occupation, a fact that provides social inequality and conflicts in the urban land occupation, as well as excluding factors. This study aims to present a general portrait of the process of occupation in the Fazenda Santa Marta, in Santa Maria, including its 7 (seven) settlements which are: Loteamento Alto da Boa Vista, Loteamento Marista, Loteamento Sete de Dezembro, Loteamento Dez de Outubro, Loteamento Dezoito de Setembro, Loteamento Pôr do Sol, and Loteamento Núcleo Central. Therefore, the temporal analysis for this study starts with the 1991 occupation, rescuing its history process, as well as the evidence indicating that a certain amount of poverty is associated to the lack of infrastructure. This way, there is a focus on the analysis of the social spatial aspects of the evolving process, on the historic process and on the understanding of social movements, as well as to highlight nowadays the context of the settlements. The methodology used had a theoretical basis limited by the studied area and a cartographic base. With this bibliographic research, it was possible to identify the current structure of Bairro Nova Santa Marta, and also how the process of irregular occupation is understood within it. In this process, predominates the expansion of the areas and an increase of poverty and need for basic services, because the population of the settlements is growing considerably, and the poverty does not manifest only in the lack of basic social services, but in the absence of sociability and environmental resources that can could help the residents. Finally, all the progress of men studied here shows the characteristic urban lifestyle and everyday life, of contemporary life.